Temporal trends of morbidities, and risk and protective factors for noncommunicable diseases in elderly residents in Brazilian capitals - Alanna Gomes da Silva; Fabiana Martins Dias de Andrade; Edmar Geraldo Ribeiro; Deborah Carvalho Malta (Associação Brasileira de Pós-Graduação em Saúde Coletiva, 2023)
ABSTRACT Objective: To analyze the temporal trends of prevalence of morbidities, risk and protection factors for noncommunicable diseases in elderly residents in Brazilian capitals between 2006 and 2021. Methods: A time series study with data from the Surveillance System of Risk and Protective Factors for Chronic Diseases by Telephone Inquiry. The variables analyzed were: high blood pressure, diabetes, smoking, overweight, obesity, consumption of alcoholic beverages, soft drinks, fruits and vegetables, and the practice of physical activity. Prais-Winsten regression and Interrupted Time Series from 2006 to 2014 and 2015 to 2021 were used. Results: From 2006 to 2021, for the total elderly population, there was an increase in diabetes (19.2 to 28.4%), alcohol consumption (2.5 to 3.2%), overweight (52.4 to 60.7%) and obesity (16.8 to 21.8%), and a reduction in the prevalence of smokers (9.4 to 7.4%) and in soft drink consumption (17 to 8.7%). By the interrupted series, between 2015 and 2021, there was stability in the prevalence of diabetes, female smokers, overweight among men, obesity in the total and male population, and soft drink consumption. Conclusion: Over the years, there have been changes and worsening in the indicators analyzed, such as an increase in diabetes, alcohol consumption, overweight, and obesity, which reinforces the importance of continuous monitoring and sustainability programs to promote the health, especially in the context of economic crisis, austerity, and COVID-19 pandemic.